Preparation method of multifunctional polyvinyl composite film and application of multifunctional polyvinyl composite film in food preservation
By combining silver metal organic frame (Ag@MOF) powder with carboxymethyl chitosan (CMCS) and tannin (TA), a multifunctional composite film is formed, which solves the problem of poor performance of polyethylene films in blocking oxygen and ultraviolet rays, and efficient food preservation is achieved and the shelf life of cold fresh meat is extended.
Patent Information
- Application Number
- CN202411837111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-28
AI Technical Summary
Existing polyethylene films have poor performance in blocking oxygen and ultraviolet rays, and lack antibacterial and antioxidant activities, making it difficult to achieve long-term food preservation.
Silver metal organic frame (Ag@MOF) powder was prepared by hydrothermal method, and combined with carboxymethyl chitosan (CMCS) and tannin acid (TA) to form a multifunctional composite film, coated onto a polyethylene film treated with oxygen plasma to prepare a multifunctional polyvinyl composite film with high barrier, antibacterial and antioxidant properties.
This multifunctional composite film shows excellent barrier properties, mechanical properties, antibacterial and antioxidant activities in food preservation, and can extend the shelf life of cold fresh meat by 5-6 days.
Smart Images

Figure CN119529357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of active packaging materials, and in particular to a preparation method of a multifunctional polyethylene-based composite film and application of the film in food preservation. Background Art
[0002] As people pay more attention to health, they hope to reduce chemical additives in food processing as much as possible. This poses new challenges to the safety and quality of food storage from the processing production area to the sales market. The food sold must be fresh and easy to store. Therefore, it is necessary to develop a packaging film material with antibacterial and antioxidant properties.
[0003] Polyethylene film is widely used due to its good moisture barrier properties, high impact strength, excellent mechanical properties and low price. It has become the most common cling film on the market due to its timely supply of raw materials and mature preparation technology. However, polyethylene has poor barrier properties against oxygen and ultraviolet rays, and it does not have antibacterial and antioxidant activity. Therefore, its effect on food preservation is limited, and it is difficult to effectively preserve food for a long time. It is a common method to introduce active ingredients into the film or to coat and fix the active ingredients on the surface of the film to modify the PE cling film to increase its activity and barrier capacity.
[0004] Chitosan (CS) is widely available, low-cost, biodegradable, and has good film-forming properties and antibacterial activity. It can effectively improve the antibacterial ability of PE when combined with PE. Wong et al. coated chitosan / gallic acid on the surface of plasma-treated PE to prepare an antibacterial cling film (Food Chemistry 2020, 329,126989). PE modified with chitosan / gallic acid has excellent antibacterial properties and can be used for fresh-keeping packaging of tilapia fillets to effectively extend its shelf life. However, CS can only be dissolved in acidic solutions, has limited antibacterial ability, and has weak barrier properties against oxygen and ultraviolet rays. Its derivative, carboxymethyl chitosan (CMCS), retains its excellent properties while also having good solubility and can be directly dissolved in water. The carboxyl groups on its molecular chain make it easier to interact with other substances.
[0005] Silver metal organic framework (Ag@MOF) has attracted much attention in the field of food packaging due to its broad-spectrum antibacterial activity, low toxicity and good stability. However, it has poor compatibility with polymers and poor dispersibility in general polymer film matrices, resulting in problems such as weak bonding between Ag@MOF and the film matrix, easy loss and insufficient mechanical properties of the film. Therefore, it is of great significance to develop a preparation method for a composite film with antibacterial and antioxidant activity, safe ingredients and that can be used in food preservation packaging. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a multifunctional polyethylene-based composite film and its application in food preservation. The multifunctional polyethylene-based composite film of the present invention has the multifunctional properties of high barrier (oxygen barrier, ultraviolet barrier), antibacterial and antioxidation, and can be used for food preservation.
[0007] The method for preparing the multifunctional polyethylene-based composite film of the present invention comprises the following steps:
[0008] Step 1: Preparation of Ag@MOF powder by hydrothermal method
[0009] Weigh a certain amount of silver nitrate and dissolve it in deionized water. After it is completely dissolved, add a certain amount of imidazole, heat and stir for a certain period of time, centrifuge with ethanol, wash, remove excess impurities, and obtain a white crystalline powder after drying. Save the sample for later use.
[0010] Step 2: Preparation of modified mixed solution
[0011] A certain amount of carboxymethyl chitosan was added into pure water, heated and stirred to fully dissolve it; an appropriate amount of Ag@MOF was added into the carboxymethyl chitosan solution, and stirring was continued at room temperature for 30-120 minutes, and then tannic acid (TA) solution was added dropwise into the system, and finally propylene glycol was added into the system, stirred at room temperature and allowed to stand for degassing to obtain a CMCS / TA / Ag@MOF mixed solution.
[0012] At the same time, a certain amount of carboxymethyl chitosan was added into pure water, heated and stirred to fully dissolve it; a certain concentration of tannic acid (TA) solution was added dropwise into the solution, and finally propylene glycol was added into the system, stirred at room temperature and allowed to stand for degassing to obtain a CMCS / TA mixed solution for comparison.
[0013] Step 3: Preparation of PE / CTA multifunctional composite membrane
[0014] The polyethylene film is cut into the required size and placed in an oxygen plasma tester for oxygen plasma treatment to obtain a polyethylene film with good hydrophilicity on the surface; the CMCS / TA / Ag@MOF mixed solution obtained in step 2 is coated on the polyethylene film after oxygen plasma treatment at a coating speed of 60-100 mm / min, and dried at 60°C for 3-4 h to obtain a multifunctional composite film.
[0015] In step 2, the preparation method of carboxymethyl chitosan solution is as follows: weigh 2 g of carboxymethyl chitosan, add it into 80-100 mL of pure water, and stir at 60° C. for 2 h to 3 h.
[0016] In step 2, the mass ratio of tannic acid to carboxymethyl chitosan is (0.01-0.1):1; the mass ratio of Ag@MOF to carboxymethyl chitosan is (0.01-0.08):1.
[0017] Furthermore, the mass of tannic acid is 4% of the mass of carboxymethyl chitosan.
[0018] In step 3, the power of the oxygen plasma treatment is 30-80 W, and the treatment time is 30-60 s.
[0019] Application of the multifunctional polyethylene-based composite film of the present invention in food preservation.
[0020] The multifunctional composite film of the present invention was cut into a 10 cm × 10 cm square, and covered on a polypropylene plastic box containing a chilled fresh meat sample, with the PE side facing upward to seal the polypropylene box, and placed at 4°C to observe and record changes in the sample. The sample was taken out at regular intervals, and its external light and color changes were observed and recorded, and its juice loss rate, pH value, total bacterial count, volatile basic nitrogen and malondialdehyde were tested.
[0021] The beneficial effects of the present invention are embodied in:
[0022] 1. The multifunctional polyethylene-based composite film of the present invention has good barrier properties (oxygen, water vapor and UV rays), excellent mechanical properties, antibacterial and antioxidant advantages, and can be used for cold fresh meat preservation packaging. The Ag@MOF particles prepared by the hydrothermal method have excellent antibacterial ability.
[0023] 2. Further prepare a multifunctional polyethylene-based composite film by a doctor blade coating method. The multifunctional polyethylene-based composite film prepared by this method not only has good mechanical properties, excellent barrier properties (oxygen, water vapor and UV rays), etc., but also the carboxymethyl chitosan matrix has the advantages of being colorless, non-toxic, and degradable. It can not only effectively load the Ag@MOF particles, but also can produce a cross-linking reaction with Ag@MOF together with tannic acid, reducing the release of anions, thereby reducing the toxicity of the film.
[0024] 3. The multifunctional polyethylene-based composite film of the present invention has excellent barrier properties (oxygen, water vapor and UV rays), mechanical properties, and antibacterial and antioxidant activities. It can be used for the fresh-keeping packaging of cold fresh meat and extend its shelf life by 5-6 days. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Scanning electron microscope image of Ag@MOF particles.
[0026] Figure 2 Infrared absorption spectra of Ag@MOF particles and films of different components.
[0027] Figure 3 XPS spectra of different samples and accurate spectra of O1s and N1s
[0028] Figure 4 Scanning electron microscope images of the plane (upper row) and cross-section (lower row) of different films.
[0029] Figure 5 is the absorption capacity of ultraviolet light by the films obtained with different mass fractions of tannic acid.
[0030] Figure 6 DPPH free radical scavenging rate (A) and ABTS free radical scavenging rate (B) of the films obtained at different tannic acid mass fractions.
[0031] Figure 7 Tensile strength and elongation at break of the films obtained at different Ag@MOF mass fractions.
[0032] Figure 8 is the oxygen permeability of the films obtained at different Ag@MOF mass fractions.
[0033] Fig. 9 is the water vapor permeability of the films obtained at different Ag@MOF mass fractions.
[0034] Fig.10 DPPH radical scavenging rate (A) and ABTS radical scavenging rate (B) of the films obtained at different Ag@MOF mass fractions.
[0035] Fig.11 The inhibition zones of the films obtained at different Ag@MOF mass fractions against the mixed bacterial population of Escherichia coli and Staphylococcus aureus.
[0036] Fig.12 This is a graph showing the appearance and color changes of fresh meat within a certain period of time after being packaged with PE / CTA active film with 4% Ag@MOF mass fraction and PE film at 4°C.
[0037] Fig.13 This is a comparison of the mass loss of fresh meat within a certain period of time after packaging it with PE / CTA active film with 4% Ag@MOF mass fraction and PE film at 4°C.
[0038] Fig.14 This is a comparison of the TVC changes of fresh meat within a certain period of time after being packaged in PE / CTA active film with 4% Ag@MOF mass fraction and PE film at 4°C.
[0039] Fig.15 This is the pH change ratio of fresh meat packaged with PE / CTA active film with 4% Ag@MOF mass fraction and PE film at 4°C within a certain period of time.
[0040] Fig.16This is a comparison of the changes in volatile basic nitrogen in fresh meat within a certain period of time after packaging it with PE / CTA active film with a Ag@MOF mass fraction of 4% and PE film at 4°C.
[0041] Fig.17 This is a comparison of the changes in malondialdehyde in fresh meat within a certain period of time after packaging it with PE / CTA active film with 4% Ag@MOF mass fraction and PE film at 4°C. DETAILED DESCRIPTION
[0042] The following is a detailed description of the embodiments and the attached Figure 1-17 , further illustrating the present invention.
[0043] Embodiment 1:
[0044] 1. Weigh 0.17 g of AgNO3 and dissolve it in 100 mL of deionized water. After AgNO3 is completely dissolved, add 1 g of imidazole and place the solution in a 30°C constant temperature water bath and stir for 2 h. Centrifuge with ethanol and wash three times at a centrifugal speed of 10,000 rpm for 10 min to remove excess impurities. Dry in a 60°C forced air drying oven for 15 h until dry to obtain white powdery crystalline Ag@MOF. Save the sample for later use.
[0045] 2. Weigh 2 g of CMCS using an electronic balance and add it to a beaker containing 80 mL of deionized water. Place the beaker on a constant temperature magnetic stirrer and stir at room temperature for 2 h to obtain a CMCS solution.
[0046] 3. Accurately weigh 0.02 g of the Ag@MOF powder prepared above using an electronic balance, add it to the above CMCS solution, stir it with a constant temperature magnetic stirrer at room temperature for 1 h, then put the beaker into an ultrasonic cleaner and ultrasonicate it for 1 h to obtain a uniform dispersion (the mass ratio of Ag@MOF to CMCS is 1%).
[0047] 4. Accurately weigh 0.08g of TA powder and add it to a beaker containing 20 mL of deionized water. Stir at room temperature for 1 hour to fully dissolve it. Then, add the TA solution dropwise to the CMCS and Ag@MOF mixed solution while stirring, and continue stirring for 30 minutes. Finally, add 1mL of glycerol to the mixed solution, stir at room temperature for 30 minutes, and stand for degassing for 2 hours to obtain a CMCS / TA / Ag@MOF (CTA) mixed solution.
[0048] 5. Cut the PE film into a rectangle of 30 cm × 20 cm, and place the cut PE film into an oxygen plasma tester for oxygen plasma treatment. The treatment time is 30 s and the treatment power is 60 W. Spread the treated PE film flat on a coating machine, use a vacuum pump to dry the air at the bottom, pour the degassed CTA solution on the PE, and use a coating machine to evenly coat the solution on the PE film. Then dry it in the coating machine at 60 ° C for 3 h to prepare a PE / CTA composite active cling film.
[0049] Embodiment 2:
[0050] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0 g (mass fraction 0%), and the mass of TA powder in step 4 is 0 g (mass fraction 0%).
[0051] Embodiment 3:
[0052] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0 g (mass fraction 0%), and the mass of TA powder in step 4 is 0.02 g (mass fraction 1%).
[0053] Embodiment 4:
[0054] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0 g (mass fraction 0%), and the mass of TA powder in step 4 is 0.14 g (mass fraction 7%).
[0055] Embodiment 5:
[0056] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0 g (mass fraction 0%), and the mass of TA powder in step 4 is 0.20 g (mass fraction 10%).
[0057] Embodiment 6:
[0058] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0 g (mass fraction 0%).
[0059] Embodiment 7:
[0060] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0.04 g (mass fraction 2%).
[0061] Embodiment 8:
[0062] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0.08 g (mass fraction 4%).
[0063] Embodiment 9:
[0064] The difference between this embodiment and embodiment 1 is that the mass of Ag@MOF powder in step 3 is 0.16 g (mass fraction 8%).
[0065] Embodiment 10:
[0066] 1. Weigh 0.17 g of AgNO3 and dissolve it in 100 mL of deionized water. After AgNO3 is completely dissolved, add 1 g of imidazole and place the solution in a 30°C constant temperature water bath and stir for 2 h. Centrifuge with ethanol and wash three times at a centrifugal speed of 10,000 rpm for 10 min to remove excess impurities. Dry in a 60°C forced air drying oven for 15 h until dry to obtain white powdery crystalline Ag@MOF. Save the sample for later use.
[0067] 2. Weigh 2 g of CMCS using an electronic balance and add it to a beaker containing 80 mL of deionized water. Place the beaker on a constant temperature magnetic stirrer and stir at room temperature for 2 h to obtain a CMCS solution.
[0068] 3. Accurately weigh 0.02 g of the Ag@MOF powder prepared above using an electronic balance, add it to the above CMCS solution, stir it with a constant temperature magnetic stirrer at room temperature for 1 h, then put the beaker into an ultrasonic cleaner and ultrasonicate it for 1 h to obtain a uniform dispersion (the mass ratio of Ag@MOF to CMCS is 1%).
[0069] 4. Accurately weigh 0.08g of TA powder and add it to a beaker containing 20 mL of deionized water. Stir at room temperature for 1 hour to fully dissolve it. Then, add the TA solution dropwise to the CMCS and Ag@MOF mixed solution while stirring, and continue stirring for 30 minutes. Finally, add 1mL of glycerol to the mixed solution, stir at room temperature for 30 minutes, and stand for degassing for 2 hours to obtain a CMCS / TA / Ag@MOF (CTA) mixed solution.
[0070] 5. Cut the PE film into a rectangle of 30 cm × 20 cm, and place the cut PE film into an oxygen plasma tester for oxygen plasma treatment. The treatment time is 30 s and the treatment power is 60 W. Spread the treated PE film flat on a coating machine, use a vacuum pump to dry the air at the bottom, pour the degassed CTA solution on the PE, and use a coating machine to evenly coat the solution on the PE film. Then dry it in the coating machine at 60 ° C for 3 h to prepare a PE / CTA composite active cling film.
[0071] 6. Rinse the pork that has been cooled for 24 hours after slaughter three times with 0.85% NaCl solution aseptically to ensure uniform initial microorganisms. Cut the cold fresh meat into blocks of about 2 cm thick with a sterile knife on a clean bench and place them in a polypropylene plastic box. Cut the PE / CTA active cling film with a 4% Ag@MOF content prepared above into 10 cm × 10 cm squares and cover the polypropylene plastic box containing the cold fresh meat sample. Seal the polypropylene box with the PE side facing up and place it at 4°C. Observe and record the color changes of the samples every 2 days and compare them with ordinary PE cling film.
[0072] In step 6, the weight change is measured every 2 days, the weight loss is calculated, and a data graph is drawn.
[0073] In step 6, the pH of the fresh meat samples is tested every two days in accordance with GB / 9695.5-2008 "Determination of pH of Meat and Meat Products" and the data is plotted.
[0074] In step 6, the total colony count of the fresh meat samples is tested every 2 days in accordance with GB / 4789.2-2022 "Determination of Total Colony Count" and the data is plotted.
[0075] In step 6, the volatile basic nitrogen in the sample is tested by the microdiffusion method every 2 days in accordance with GB / 5009.228-2016 "Determination of Volatile Basic Nitrogen in Food", and the data is plotted.
[0076] In step 6, the malondialdehyde in the sample is tested by spectrophotometry every 2 days in accordance with GB / 5009.181-2016 "Determination of malondialdehyde in food", and the data is plotted.
[0077] The morphology of the prepared Ag@MOF powder was observed by scanning electron microscopy (SEM). Figure 1 ). As can be seen from the figure, the prepared Ag@MOF is a flake or block particle structure with a length of about 300-800 nm and a width of about 500 nm. Most of them are gathered together and have a relatively smooth surface.
[0078] Figure 2 Figure 1 shows the infrared spectra of different samples, including Ag@MOF powder, pure carboxymethyl chitosan film, CTA film with 2% Ag@MOF mass fraction, PE film treated with oxygen plasma, and PE / CTA composite active film. For Ag@MOF, the infrared absorption spectra at 3116, 1458, and 1649 cm -1 The peaks at 1306 and 1279 cm are the absorption vibration peaks of NH, C=N and CN on imidazole; -1The peaks at 751 cm are the bending vibration and asymmetric stretching vibration peaks of CO. -1 The peaks at 3276 cm-1 are the Ag-N stretching vibration absorption peaks. The appearance of these vibration peaks indicates that Ag@MOF has been successfully prepared. The spectrum curve of pure carboxymethyl chitosan film shows that the wave number is 3276 cm-1. -1 The peak is due to the OH bond stretching absorption vibration absorption peak; the wave number is 1556 cm -1 A broad peak appears at and is caused by the overlap of the NH bending vibration of the amino group; the wave number is 1030 cm -1 The peaks at 1579 cm-1 are due to the stretching and contraction of COC. Compared with the CMCS membrane, the characteristic peaks on the CTA composite membrane appear at wave numbers of 1579, 1409, 1312, and 1028 cm-1. -1 This indicates that the addition of Ag@MOF causes the absorption peak position of the CMCS film to shift. There is a hydrogen bond or even a cross-linking effect between them. The characteristic peak of Ag@MOF is not obvious because the amount of Ag@MOF is relatively small. -1 The obvious peak at 3383 cm-1 indicates that oxygen plasma treatment produces hydrophilic -OH and -COOH on the surface. -1 The peak shifted to 3330 cm -1 , 1028 cm -1 The peak at 1051 cm -1 This indicates that there is a strong hydrogen bond between PE and CTA.
[0079] Figure 3 The X-ray diffraction spectra (XPS) of different samples and the O1s and N1s fine spectra of more samples. In general, each sample has the binding energy of C 1s, O1s and N1s. In addition, the characteristic peak of Ag 3d also appears on Ag@MOF. From the O 1s fine spectrum, 531.7 eV in CMCS corresponds to -COO - The C=O binding energy in the figure and 532.5 eV correspond to C-OH; for CMCS / TA, the C=O binding energy shifts to 531.6 eV and the C-OH binding energy shifts to 532.3 eV, indicating that there is a hydrogen bond between CMCS and TA. -The binding energy of C=O in the graph appears at 531.2 eV, the binding energy of C-OH shifts to 532.0 eV, and the binding energy of CO appears at 532.7 eV, which indicates that Ag@MOF interacts with CMCS / TA. From the fine spectrum of N 1s, characteristic peaks of CN (398.9 eV) and Ag-N (400.0 eV) appear on the Ag@MOF sample, respectively. 399.2 eV and 399.7 eV in CMCS correspond to the binding energies of C-NH2 and CNC, respectively. For CMCS / TA, the binding energies of C-NH2 and CNC appear at 399.1 eV and 399.7 eV, respectively, indicating that TA and CMCS may form hydrogen bonds through -OH on TA and -NH2 on CMCS. After the addition of Ag@MOF, the binding energy of CNC shifted to 399.6 eV, and the characteristic peak of Ag-N appeared at 400.2 eV, which may be due to the formation of N-Ag-O bonds between Ag@MOF and CMCS.
[0080] Figure 4 The surface and cross section of pure polyethylene film, CTA composite film and PE / CTA composite active film observed under an electron scanning microscope. Figure 4 It can be seen that the surface of PE is smooth and flat, and the cross section is tight. Tiny particles appear on the surface of the CTA film, and these particles can also be observed from the cross section, which shows that Ag@MOF is evenly dispersed in the CMCS matrix, and the presence of Ag@MOF does not affect the CMCS film formation. The surface of the PE / CTA composite active film is similar to that of the CTA film, with evenly dispersed Ag@MOF particles. The presence of Ag@MOF can also be seen from the cross section, and there is a clear boundary between the PE film and the CTA film.
[0081] In Example 1-5, the mass fraction of Ag@MOF in step 3 is 0%, the mass fraction of TA in step 4 is changed, and the other parameters remain unchanged. Controlling the mass fraction of TA will affect the ultraviolet blocking ability and antioxidant performance of the film. Figure 5 The UV absorption capacity test results of CMCS / TA active films obtained at different TA mass fractions. With the increase of TA content, the UV absorption capacity of the film gradually increases; when the TA content increases to 4%, the film can absorb 100% of UV light. Figure 6 The antioxidant capacity data of the prepared CMCS / TA active membranes with different TA contents are shown in Figure 2. Figure 6It can be seen that with the increase of TA content, the DPPH free radical scavenging rate and ABTS free radical scavenging rate of the film gradually increased and tended to be stable, and when the TA content was 4%, the DPPH free radical scavenging rate and ABTS free radical scavenging rate of the film reached 90.2% ± 2.3% and 91.2% ± 2.1%, respectively. With the continuous increase of TA content, the DPPH free radical scavenging rate and ABTS free radical scavenging rate of the film increased very little and remained stable.
[0082] In Examples 6-9, the mass fractions of Ag@MOF in step 3 are different, and the other parameters remain unchanged. Controlling the mass fraction of Ag@MOF will affect the mechanical properties, barrier capacity, antibacterial and antioxidant properties of the film. Figure 7 The mechanical properties test results of the PE / CTA composite active film obtained at different Ag@MOF mass fractions show that with the increase of Ag@MOF content, the tensile strength of the film first increases and then decreases; when the Ag@MOF content increases to 4%, the tensile strength is the largest; and the elongation at break gradually increases. This may be because hydrogen bonds are formed between the tannic acid and carboxymethyl chitosan of Ag@MOF, and cross-linking is also produced, which enhances the interaction between molecules and makes the film denser. When the Ag@MOF content reaches 4%, its interaction reaches the strongest, and further increasing its dosage can no longer increase its tensile strength.
[0083] Figure 8 and Fig. 9 The following is a data graph of the oxygen and water vapor permeability of the prepared PE / CTA composite active membrane with different Ag@MOF contents and pure PE membrane. It can be seen from the figure that compared with the pure PE film, the oxygen permeability of the PE / CTA composite active membrane is significantly reduced, and with the increase of the Ag@MOF content, the oxygen permeability gradually decreases. This is because carboxymethyl chitosan can form a thin film with good density on the surface of PE, which hinders the O2 molecules in the air from passing through the PE / CTA composite membrane, thereby enhancing the film's barrier performance to O2. In addition, the water vapor permeability also shows the same trend as the oxygen permeability. This is because the PE film has good water vapor barrier properties, and the addition of Ag@MOF and tannic acid will undergo a cross-linking reaction with carboxymethyl chitosan, making the structure of the film tighter, thereby hindering the entry of water molecules and improving the film's barrier ability to water vapor. From Fig.10 It can be seen that the addition of Ag@MOF does not affect the antioxidant capacity of the PE / CTA active film, because the antioxidant capacity of the film is mainly achieved by tannic acid. The antibacterial ability of the film increases with the increase of Ag@MOF content, because Ag@MOF has good antibacterial properties and has excellent inhibitory effects on Escherichia coli and Staphylococcus aureus ( Fig.11 ).
[0084] In Example 6, the preservation effect of PE / CTA active membrane with 4% Ag@MOF added on fresh meat samples was investigated in different aspects. Fig.12 It can be seen that the color of the fresh meat sealed with PE film gradually changes from bright red to yellow-brown to reddish brown as the storage time increases, while the color of the fresh meat packaged with PE / CTA changes from bright red to yellow-brown, and only starts to turn yellow-brown on the 8th day. Fig.13 This means that the juice loss rate of fresh meat packaged with PE / CTA film is lower than that of fresh meat packaged with PE film during the entire storage period, and after 14 days, its quality loss is less than 5%. Fig.14 The results showed that due to the excellent antibacterial properties of Ag@MOF, the number of bacteria in the fresh meat packaged with PE / CTA active film with 4% Ag@MOF addition was still lower than the number specified by the national standard (10 6 ), while the number of bacteria in cold fresh meat packaged with ordinary PE film has reached the level specified by the national standard on the 6th day. Fig.15 It can be seen that the pH of the fresh meat packaged with PE / CTA active film was still lower than the national standard level (6.6) at 12 days, while the number of bacteria in the fresh meat packaged with ordinary PE film reached 6.6 at the 6th day. Fig.15 It can be seen that the pH of the fresh meat packaged with PE / CTA active film was still lower than the national standard level (6.6) at 12 days, while the pH of the fresh meat packaged with ordinary PE film reached 6.6 at the 6th day. This is because the excellent antibacterial properties of Ag@MOF inhibit the growth and reproduction of bacteria, thereby indirectly reducing the decomposition of nutrients of fresh meat by microorganisms, resulting in a slow increase in pH. Fig.16 It can be seen that the TVB-N level of the chilled meat packaged with PE / CTA active film was in a fresh state (15 mg / 100g) at 12 days, while the TVB-N of the chilled meat packaged with ordinary PE film exceeded 15 mg / 100g on the 6th day and exceeded 20 mg / 100g on the 8th day, indicating that the sample was corrupted and could no longer be eaten. Fig.17 It can be seen that the TBARS level of fresh meat packaged with PE / CTA active film was in the fresh state (less than 1.0 mg MDA / kg) at 12 days, while the TBARS level of fresh meat packaged with ordinary PE film exceeded 1.0 mg MDA / kg at 10 days. Figure 11-14 It can be seen that compared with ordinary PE film, the shelf life of fresh meat packaged in PE / CTA active film with 4% Ag@MOF addition can be extended by about 6 days.
[0085] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.
[0086] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a multifunctional polyethylene-based composite film, characterized in that The steps include: Step 1: Preparation of Ag@MOF powder by hydrothermal method Dissolve silver nitrate in deionized water, add imidazole after it is completely dissolved, heat and stir, centrifuge with ethanol, wash, remove excess impurities, dry to obtain white crystalline powder, and store for later use; Step 2: Preparation of modified mixed solution Carboxymethyl chitosan was added into pure water, heated and stirred to fully dissolve; Ag@MOF was added into the carboxymethyl chitosan solution, and stirring was continued at room temperature for 30-120 minutes, and then tannic acid solution was added dropwise into the system, and finally propylene glycol was added into the system, stirred at room temperature and allowed to stand for degassing to obtain a CMCS / TA / Ag@MOF mixed solution; Step 3: Preparation of PE / CTA multifunctional composite membrane The polyethylene film is cut into the required size and placed in an oxygen plasma tester for oxygen plasma treatment to obtain a polyethylene film with good hydrophilicity on the surface; the CMCS / TA / Ag@MOF mixed solution obtained in step 2 is coated on the polyethylene film after oxygen plasma treatment, and a multifunctional composite film is obtained after drying.
2. The preparation method according to claim 1, characterized in that: In step 2, the preparation method of carboxymethyl chitosan solution is as follows: weigh 2 g of carboxymethyl chitosan, add it into 80-100 mL of pure water, and stir at 60° C. for 2 h to 3 h.
3. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of tannic acid to carboxymethyl chitosan is (0.01-0.1):1; the mass ratio of Ag@MOF to carboxymethyl chitosan is (0.01-0.08):
1.
4. The preparation method according to claim 3, characterized in that: The mass of tannic acid is 4% of the mass of carboxymethyl chitosan.
5. The preparation method according to claim 1, characterized in that: In step 3, the power of the oxygen plasma treatment is 30-80 W, and the treatment time is 30-60 s.
6. The preparation method according to claim 1, characterized in that: In step 3, the CMCS / TA / Ag@MOF mixed solution obtained in step 2 is coated on the polyethylene film treated with oxygen plasma at a coating speed of 60-100 mm / min.
7. Use of the multifunctional polyethylene-based composite film prepared by the preparation method according to any one of claims 1 to 6 in food preservation.
8. The use according to claim 7, characterized in that: The multifunctional polyethylene-based composite film is used for fresh-keeping packaging of cold fresh meat.
Citation Information
Cited By
Polyvinyl chitosan and tannic acid composite active membrane as well as preparation method and application thereof
CN122011473A
Polyvinyl chitosan tannic acid composite active film, preparation method thereof and application thereof
CN122011473B